Performance of turmeric (Curcuma longa L.) varieties in the hill zone of Karnataka, India - UTHAIAH, K S SHESHAGIRI, B C (Journal of Spices and Aromatic Crops, 1994)
A field experiment was conducted at Mudigere (Karnataka, India) to assess the yield performance of six elite turmeric (Curcuma longa) varieties under rainfed conditions. The yield of fresh turmeric was maximum in BSR-1 (16.57 tfha) followed by Waigon (15.45 tfha). BSR-1 was also superior in growth attributes.